2022
DOI: 10.3389/fpsyt.2022.875722
|View full text |Cite
|
Sign up to set email alerts
|

Effect of -NBOMe Compounds on Sensorimotor, Motor, and Prepulse Inhibition Responses in Mice in Comparison With the 2C Analogs and Lysergic Acid Diethylamide: From Preclinical Evidence to Forensic Implication in Driving Under the Influence of Drugs

Abstract: In the last decade, the market for new psychoactive substances has been enriched by numerous psychedelic phenethylamines, which mimic the psychoactive effect of lysergic acid diethylamide (LSD). In particular, the -NBOMe series, which are more potent than their 2C compounds analogs, are considered worthy substitutes for LSD by users. The purpose of this study was to assess the effects of 25H-NBOMe and its halogenated derivatives (25I-NBOMe and 25B-NBOMe) in comparison to their 2C compounds analogs and LSD on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 76 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…When administered subcutaneously, 25I-NBOMe (0.03–3 mg/kg) produced a bell-shaped effect on C57BL/6J mouse activity [ 40 ]. In line with this finding, the researchers have also shown that low (0.001–1 mg/kg) and moderate (0.1–1 mg/kg) doses of 25I-NBOMe increase mobility, while a high dose (10 mg/kg) causes a sharp decline in the spontaneous motor activity of male ICR mice [ 41 ]. Similarly, 25B-NBOMe inhibited the motor activity of Wistar Han rats measured in an open field (0.3–3 mg/kg) [ 37 ].…”
Section: Nbomesmentioning
confidence: 67%
“…When administered subcutaneously, 25I-NBOMe (0.03–3 mg/kg) produced a bell-shaped effect on C57BL/6J mouse activity [ 40 ]. In line with this finding, the researchers have also shown that low (0.001–1 mg/kg) and moderate (0.1–1 mg/kg) doses of 25I-NBOMe increase mobility, while a high dose (10 mg/kg) causes a sharp decline in the spontaneous motor activity of male ICR mice [ 41 ]. Similarly, 25B-NBOMe inhibited the motor activity of Wistar Han rats measured in an open field (0.3–3 mg/kg) [ 37 ].…”
Section: Nbomesmentioning
confidence: 67%
“…The effects of AKB48 were evaluated using a series of behavioural tests (visual object and visual placing response test, acoustic test, tactile test, tail pinch test, core temperature test, breath rate test, and mobility time test) routinely used in our laboratories to describe the effects of synthetic cannabinoids in mice (Bilel et al, 2020;Canazza et al, 2016Canazza et al, , 2017Ossato et al, 2015Ossato et al, , 2016Vigolo et al, 2015) and widely validated for the preclinical characterization of the pharmacotoxicological effects of NPSs in rodents (Arfè et al, 2021;Bilel et al, 2021Bilel et al, , 2022De-Giorgio et al, 2020;Ossato et al, 2018;Tirri et al, 2022).…”
Section: Behavioural Studiesmentioning
confidence: 99%